Insulating glue, preparation method thereof and photovoltaic module
By optimizing the components of the insulating glue, including polyurethane acrylate and silane coupling agent, the bonding force between the glue in the back contact battery assembly and the battery surface is improved, the problem of low peel strength is solved, and the stability and insulation of the assembly are enhanced. performance.
Patent Information
- Application Number
- CN202411497017.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-10
AI Technical Summary
When used in the back contact battery assembly, the existing insulating glue has low peel strength, making it difficult to meet the high requirements of the battery assembly for insulating glue, affecting the insulation performance and stability of the assembly.
Using polyurethane acrylate, isoborna acrylate, modified monomer, initiator, defoaming agent, leveling agent and transparent inorganic material insulating glue, improve the glue and battery surface by optimizing components and adding silane coupling agent. Bonding force enhances peel strength.
It significantly improves the bonding force between the glue and the battery surface, meets the high requirements of the back contact battery module for insulating glue, enhances the stability and reliability of the components, and avoids short-circuit failures.
Smart Images

Figure CN119286461A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of photovoltaic technology, and mainly to an insulating glue and a preparation method thereof, and a photovoltaic module. Background Art
[0002] With the continuous development of solar cell technology, back-contact cell modules have been widely used in the photovoltaic field due to their unique structural and performance advantages. The back structure of the back-contact cell module is complex, and it needs to have good insulation and adhesion properties to ensure the stability and reliability of the cell module. However, when the existing insulating glue is applied to the back-contact cell module, there are some problems, especially the problem of low peel strength, which seriously affects the performance and service life of the cell module.
[0003] Common insulating glues on the market are mainly thermosetting glue and UV light-curing glue. Although thermosetting glue has high adhesion and stability, its curing time is long (180℃8min) and the curing temperature is high, which not only increases the production cost but also limits the production efficiency. Although UV light-curing glue has a fast curing speed (no more than 3s), its peel strength is often low, which makes it difficult to meet the high requirements of back-contact battery components for insulating glue. Specifically, when the existing UV light-curing insulating glue is applied to back-contact battery components, due to the uneven back of the battery, the glue is difficult to fully contact and fill the battery surface, resulting in low peel strength and easy separation of the glue film and glue, which not only affects the insulation performance of the battery component, but may also cause short circuits and other faults in the battery component during use, seriously affecting its stability and reliability.
[0004] In order to solve the problem of low bonding strength between insulating glue and batteries, the present application provides an insulating glue, a preparation method thereof, and a photovoltaic module. Summary of the invention
[0005] In order to solve the problem of low bonding strength between insulating glue and battery, the present application provides an insulating glue and a preparation method thereof and a photovoltaic module. The insulating glue comprises polyurethane acrylate, isobornyl acrylate, modified monomer, initiator, defoamer, leveling agent and transparent inorganic material, wherein the mass fraction of polyurethane acrylate in the insulating glue is 55-67%, the mass fraction of isobornyl acrylate is 1-10%, the mass fraction of modified monomer is 10-20%, the mass fraction of initiator is 1-4%, the mass fraction of defoamer is 0.1-0.3%, the mass fraction of leveling agent is 1-3%, and the mass fraction of transparent inorganic material is 3-6%.
[0006] The low Tg matrix resin uses polyurethane acrylate, which has good flexibility and adhesion properties. By optimizing the components of the glue, the bonding force between the glue and the battery surface is improved, and the peel strength is significantly improved, which can meet the high requirements of the back contact battery assembly for the insulating glue and solve the problem of low bonding force between the insulating glue and the battery.
[0007] Optionally, the transparent inorganic material is fumed silica.
[0008] Optionally, the insulating glue further comprises a silane coupling agent, and the mass fraction of the silane coupling agent in the insulating glue is 0.5-2%.
[0009] Optionally, the modified monomer includes tetrahydrofuran acrylate and polyethylene glycol monomethacrylate phosphate, and in the insulating glue, the mass fraction of tetrahydrofuran acrylate is 5-10%, and the mass fraction of polyethylene glycol monomethacrylate phosphate is 5-10%.
[0010] Optionally, the initiator includes 2,4,6-trimethylbenzoyldiphenylphosphine oxide.
[0011] Optionally, the defoaming agent includes fatty acid ester, and the leveling agent includes isophorone.
[0012] The modified monomers include tetrahydrofuran acrylate and polyethylene glycol monomethacrylate phosphate to improve the crosslinking density and weather resistance of the glue; the active diluent includes isobornyl acrylate to adjust the viscosity and curing speed of the glue; the initiator includes 2,4,6-trimethylbenzoyldiphenylphosphine oxide to initiate the photocuring reaction of the glue; the defoamer includes fatty acid ester to eliminate bubbles in the glue; the leveling agent includes isophorone to improve the leveling performance of the glue; fumed silica is used to improve the high temperature resistance and filling performance of the glue; and the silane coupling agent is used to improve the bonding strength between the glue and the battery surface.
[0013] The present application also provides a method for preparing insulating glue, and the preparation of the above-mentioned insulating glue specifically includes: uniformly mixing polyurethane acrylate, isobornyl acrylate, modified monomer, defoamer, leveling agent, transparent inorganic material and other additives in proportion, heating, stirring, and obtaining a slurry to be initiated; adding an initiator to the slurry to be initiated, stirring, and obtaining the insulating glue.
[0014] Optionally, the method specifically includes: uniformly mixing polyurethane acrylate, tetrahydrofuran acrylate, polyethylene glycol monomethacrylate phosphate, isobornyl acrylate, fatty acid ester, isophorone and other additives in a four-necked flask in proportion, heating to 60-90°C in an oil bath, stirring for 2-3 hours, and slowly dropping a prepolymer of fumed silica and a silane coupling agent to obtain a slurry to be initiated; stirring the slurry to be initiated for 1-2 hours, and then dropping 2,4,6-trimethylbenzoyldiphenylphosphine oxide into the slurry to be initiated, stirring for 1-2 hours, and obtaining the insulating glue.
[0015] Optionally, the method is performed in the dark, and the speed of adding 2,4,6-trimethylbenzoyldiphenylphosphine oxide is 2 s / drop.
[0016] The present application also provides a photovoltaic module, which is a BC module, and which includes the insulating glue described in any one of the above items.
[0017] The present application provides an insulating glue, a preparation method thereof and a photovoltaic module. The insulating glue includes polyurethane acrylate, isobornyl acrylate, a modified monomer, an initiator, a defoamer, a leveling agent and a transparent inorganic material. The transparent inorganic material is fumed silica, the modified monomer includes tetrahydrofuran acrylate and polyethylene glycol monomethacrylate phosphate, the initiator includes 2,4,6-trimethylbenzoyl diphenyl phosphine oxide, the defoamer includes fatty acid esters, the leveling agent includes isophorone, and the insulating glue also includes a silane coupling agent. A leveling agent is added to the glue to improve the fluidity and leveling of the glue, so that the glue can be combined with the uneven surface when printed on the back of the battery (before curing); a low Tg functional resin is added to the glue, so that the cured glue becomes soft and slightly dissolved after high-temperature curing, and further fills and combines with the battery surface, thereby increasing the bonding strength between the glue and the battery and solving the problem of low bonding strength between the insulating glue and the battery. The present application also provides a preparation method of the above-mentioned insulating glue and a photovoltaic module, wherein the photovoltaic module is a BC module, and the above-mentioned insulating glue is applied. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the embodiments are briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0019] Figure 1 A schematic diagram of the appearance of a component prepared with the acrylic light-curing adhesive provided in this application;
[0020] Figure 2 Schematic diagram of the sample to be tested in the peel strength (adhesion) experiment;
[0021] Figure 3 Schematic diagram of the method of cutting sample strips for peel strength (adhesion) experiment;
[0022] Figure 4 Schematic diagram of peeling method for peeling strength (adhesion) experiment;
[0023] Figure 5 This is a schematic diagram of the peel strength test results of the first insulating glue prepared in Example 1;
[0024] Figure 6 It is a schematic diagram of the peel strength test results of the sixth insulating glue prepared in comparative example 1;
[0025] Figure 7 This is a schematic diagram of the printing offset screen of this application. DETAILED DESCRIPTION
[0026] The following embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following embodiments do not represent all implementations consistent with the present application. They are only examples of systems and methods consistent with some aspects of the present application as detailed in the claims.
[0027] In order to solve the problem of low bonding strength between insulating glue and battery, the present application provides an insulating glue and a preparation method thereof and a photovoltaic module. The insulating glue comprises polyurethane acrylate, isobornyl acrylate, modified monomer, initiator, defoamer, leveling agent and transparent inorganic material, wherein the mass fraction of polyurethane acrylate in the insulating glue is 55-67%, the mass fraction of isobornyl acrylate is 1-10%, the mass fraction of modified monomer is 10-20%, the mass fraction of initiator is 1-4%, the mass fraction of defoamer is 0.1-0.3%, the mass fraction of leveling agent is 1-3%, and the mass fraction of transparent inorganic material is 3-6%.
[0028] The low Tg matrix resin uses polyurethane acrylate, which has good flexibility and adhesion properties. By optimizing the components of the glue, the bonding force between the glue and the battery surface is improved, and the peel strength is significantly improved, which can meet the high requirements of the back contact battery assembly for the insulating glue and solve the problem of low bonding force between the insulating glue and the battery.
[0029] Polyurethane acrylate is synthesized from isophorone diisocyanate (IPDI), pentaerythritol (PETL), polyester diol 1000, polyether diol PPG2000 and hydroxyethyl methacrylate (HEMA), the catalyst is dibutyltin dilaurate, and the inhibitor is p-hydroxyanisole.
[0030] In some embodiments, the transparent inorganic material is fumed silica. Adding colorless fumed silica can keep the UV light-cured insulating adhesive colorless and transparent. Compared with epoxy thermosetting glue, acrylic light-cured glue has excellent yellowing and transmittance performance. Specifically, the appearance of the component prepared by acrylic light-cured glue is as follows: Figure 1 As shown, no traces of glue can be observed on the appearance of the component, and the yellowing b value of the acrylic light-curing glue is less than 2, and the transmittance T value is greater than 92%; traces of glue can be observed on the appearance of the component prepared by the epoxy thermosetting glue. Among them, the b value represents the yellow phase, and the larger the value, the yellower it is. When the b value is less than 3, the yellowing is not obvious when observed with the naked eye, and when the b value is greater than 3, the yellowing is more obvious when observed with the naked eye; the light transmittance T value is a parameter that describes the ability of light to pass through the material, which is the ratio of the intensity of the transmitted light to the intensity of the incident light.
[0031] In some embodiments, the insulating glue further includes a silane coupling agent, and the mass fraction of the silane coupling agent in the insulating glue is 0.5-2%.
[0032] In some embodiments, the modified monomer includes tetrahydrofuran acrylate and polyethylene glycol monomethacrylate phosphate. In the insulating glue, the mass fraction of tetrahydrofuran acrylate is 5-10%, and the mass fraction of polyethylene glycol monomethacrylate phosphate is 5-10%.
[0033] In some embodiments, the initiator includes 2,4,6-trimethylbenzoyldiphenylphosphine oxide.
[0034] In some embodiments, the defoaming agent includes fatty acid ester, and the leveling agent includes isophorone.
[0035] The modified monomers include tetrahydrofuran acrylate and polyethylene glycol monomethacrylate phosphate to improve the crosslinking density and weather resistance of the glue; the active diluent includes isobornyl acrylate to adjust the viscosity and curing speed of the glue; the initiator includes 2,4,6-trimethylbenzoyldiphenylphosphine oxide to initiate the photocuring reaction of the glue; the defoamer includes fatty acid ester to eliminate bubbles in the glue; fumed silica is used to improve the high temperature resistance and filling performance of the glue, avoiding problems such as morphology collapse during high temperature welding; the addition of components such as leveling agent and silane coupling agent improves the wettability and bonding strength of the glue with the battery surface, so that the glue can fully fill the unevenness on the back of the battery, thereby improving the adhesion performance.
[0036] The present application also provides a method for preparing insulating glue, and the preparation of the above-mentioned insulating glue specifically includes: uniformly mixing polyurethane acrylate, isobornyl acrylate, modified monomer, defoamer, leveling agent, transparent inorganic material and other additives in proportion, heating, stirring, and obtaining a slurry to be initiated; adding an initiator to the slurry to be initiated, stirring, and obtaining the insulating glue.
[0037] In some embodiments, the method specifically includes: uniformly mixing polyurethane acrylate, tetrahydrofuran acrylate, polyethylene glycol monomethacrylate phosphate, isobornyl acrylate, fatty acid ester, isophorone and other additives in a four-necked flask in proportion, heating to 60-90°C in an oil bath, stirring for 2-3 hours, and slowly adding a prepolymer of fumed silica and a silane coupling agent to obtain a glass slurry to be initiated; stirring the slurry to be initiated for 1-2 hours, and then adding 2,4,6-trimethylbenzoyldiphenylphosphine oxide to the slurry to be initiated, stirring for 1-2 hours, and obtaining the insulating glue.
[0038] In some embodiments, the method is performed in the dark, and the speed of adding 2,4,6-trimethylbenzoyldiphenylphosphine oxide is 2 s / drop.
[0039] The present application also provides a component, which is a BC component, and the component includes the insulating glue described in any one of the above items, and the glue still does not delaminate after the component undergoes a PCT96h reliability test.
[0040] Example:
[0041] Taking the total mass percentage content of the insulating glue as 100%, the insulating glue of the embodiment is obtained by mixing according to the proportions in Table 1.
[0042] Table 1 Mass fraction ratio of each component of the insulating glue in the embodiment
[0043]
[0044]
[0045] Embodiment 1:
[0046] According to the proportion of the first insulating glue in Table 1, polyurethane acrylate, tetrahydrofuran acrylate, polyethylene glycol monomethacrylate phosphate, acrylate isobornyl, fatty acid ester and isophorone were uniformly mixed in a four-necked flask, heated to 60°C in an oil bath, stirred for 2 hours, and then slowly dripped the prepolymer of fumed silica and silane coupling agent therein to obtain a slurry to be initiated. After stirring the slurry to be initiated for 1 hour, 2,4,6-trimethylbenzoyl diphenylphosphine oxide was dripped into the slurry to be initiated at a speed of 2s / drop, and then stirred for 1 hour to obtain the first insulating glue.
[0047] Embodiment 2:
[0048] According to the proportion of the second insulating glue in Table 1, polyurethane acrylate, tetrahydrofuran acrylate, polyethylene glycol monomethacrylate phosphate, acrylate isobornyl, fatty acid ester and isophorone were uniformly mixed in a four-necked flask, heated to 90°C in an oil bath, stirred for 3 hours, and then slowly dripped the prepolymer of fumed silica and silane coupling agent therein to obtain a slurry to be initiated. After stirring the slurry to be initiated for 2 hours, 2,4,6-trimethylbenzoyl diphenylphosphine oxide was dripped into the slurry to be initiated at a speed of 2s / drop, and then stirred for 2 hours to obtain a second insulating glue.
[0049] Embodiment three:
[0050] According to the proportion of the third insulating glue in Table 1, polyurethane acrylate, tetrahydrofuran acrylate, polyethylene glycol monomethacrylate phosphate, acrylate isobornyl ester, fatty acid ester and isophorone were uniformly mixed in a four-necked flask, heated to 70°C in an oil bath, stirred for 2.5 hours, and then slowly dripped the prepolymer of fumed silica and silane coupling agent therein to obtain a slurry to be initiated. After stirring the slurry to be initiated for 1.5 hours, 2,4,6-trimethylbenzoyl diphenylphosphine oxide was dripped into the slurry to be initiated at a speed of 2s / drop, and then stirred for 1.5 hours to obtain a third insulating glue.
[0051] Embodiment 4:
[0052] According to the proportion of the fourth insulating glue in Table 1, polyurethane acrylate, tetrahydrofuran acrylate, polyethylene glycol monomethacrylate phosphate, acrylate isobornyl ester, fatty acid ester and isophorone were uniformly mixed in a four-necked flask, heated to 60°C in an oil bath, stirred for 3 hours, and then slowly dripped the prepolymer of fumed silica and silane coupling agent therein to obtain a slurry to be initiated. After stirring the slurry to be initiated for 2 hours, 2,4,6-trimethylbenzoyl diphenylphosphine oxide was dripped into the slurry to be initiated at a speed of 2s / drop, and then stirred for 1 hour to obtain the fourth insulating glue.
[0053] Embodiment five:
[0054] According to the proportion of the fifth insulating glue in Table 1, polyurethane acrylate, tetrahydrofuran acrylate, polyethylene glycol monomethacrylate phosphate, acrylate isobornyl, fatty acid ester and isophorone were uniformly mixed in a four-necked flask, heated to 70°C in an oil bath, stirred for 2 hours, and then slowly dripped the prepolymer of fumed silica and silane coupling agent therein to obtain a slurry to be initiated. After stirring the slurry to be initiated for 2 hours, 2,4,6-trimethylbenzoyl diphenylphosphine oxide was dripped into the slurry to be initiated at a speed of 2s / drop, and then stirred for 1 hour to obtain the fifth insulating glue.
[0055] Comparative Example:
[0056] Taking the total mass percentage content of the insulating glue as 100%, the insulating glue of the comparative example was obtained by mixing according to the proportions in Table 2.
[0057] Table 2 Mass fraction ratio of each component of insulating glue in comparative example
[0058]
[0059]
[0060] Comparative Example 1:
[0061] According to the proportion of the sixth insulating glue in Table 2, polyurethane acrylate, tetrahydrofuran acrylate, polyethylene glycol monomethacrylate phosphate, acrylate isobornyl ester, fatty acid ester and isophorone were uniformly mixed in a four-necked flask, heated to 70°C in an oil bath, stirred for 2 hours, and then slowly dripped the prepolymer of fumed silica and silane coupling agent therein to obtain a slurry to be initiated. After stirring the slurry to be initiated for 2 hours, 2,4,6-trimethylbenzoyl diphenylphosphine oxide was dripped into the slurry to be initiated at a speed of 2s / drop, and then stirred for 1 hour to obtain the sixth insulating glue.
[0062] Comparative Example 2:
[0063] According to the proportion of the seventh insulating glue in Table 2, polyurethane acrylate, tetrahydrofuran acrylate, polyethylene glycol monomethacrylate phosphate, acrylate isobornyl ester, fatty acid ester and isophorone were uniformly mixed in a four-necked flask, heated to 70°C in an oil bath, stirred for 2 hours, and then slowly dripped the prepolymer of fumed silica and silane coupling agent therein to obtain a slurry to be initiated. After stirring the slurry to be initiated for 2 hours, 2,4,6-trimethylbenzoyl diphenylphosphine oxide was dripped into the slurry to be initiated at a speed of 2s / drop, and then stirred for 1 hour to obtain the seventh insulating glue.
[0064] Comparative Example 3:
[0065] According to the proportion of the eighth insulating glue in Table 2, polyurethane acrylate, tetrahydrofuran acrylate, polyethylene glycol monomethacrylate phosphate, acrylate isobornyl ester, fatty acid ester and isophorone were uniformly mixed in a four-necked flask, heated to 70°C in an oil bath, stirred for 2 hours, and then slowly dripped the prepolymer of fumed silica and silane coupling agent therein to obtain a slurry to be initiated. After stirring the slurry to be initiated for 2 hours, 2,4,6-trimethylbenzoyl diphenylphosphine oxide was dripped into the slurry to be initiated at a speed of 2s / drop, and then stirred for 1 hour to obtain the eighth insulating glue.
[0066] Comparative Example 4:
[0067] According to the proportion of the ninth insulating glue in Table 2, polyurethane acrylate, tetrahydrofuran acrylate, polyethylene glycol monomethacrylate phosphate, acrylate isobornyl ester, fatty acid ester and isophorone were uniformly mixed in a four-necked flask, heated to 70°C in an oil bath, stirred for 2 hours, and then slowly dripped the prepolymer of fumed silica and silane coupling agent therein to obtain the slurry to be initiated. After stirring the slurry to be initiated for 2 hours, 2,4,6-trimethylbenzoyl diphenylphosphine oxide was dripped into the slurry to be initiated at a speed of 2s / drop, and then stirred for 1 hour to obtain the ninth insulating glue.
[0068] The insulating glue prepared in Examples 1 to 5 and Comparative Examples 1 to 4 was sprayed onto the back contact battery BC assembly to obtain a battery cell after treatment. The above battery cell was subjected to a peel strength (adhesion) test, and the peel strength of the battery cell was recorded. Two groups of each insulating glue level were measured in parallel.
[0069] Specifically, first, place the frosted surface of the glass upwards, and place two battery cells on it with the front side facing upwards. After applying the prepared insulating glue on the battery cells, set a release film to cover half of the battery, with the oil side of the release film facing the battery. Then, cover the second piece of transparent glass, and irradiate the battery and the glue together with an ultraviolet lamp for 5 seconds. After taking out the sample between the two glass sheets, set adhesive films on the front and back sides of the sample respectively, and set a back plate on the outermost layer of the glue surface to obtain the sample to be tested. The sample to be tested is as follows: Figure 2 As shown. Figure 3 The sample strips are cut into 20 cm × 1.5 cm specifications and clamped in the fixture of the universal material testing machine. The sample strips are kept perpendicular to the horizontal plane, and the fixture is stretched in a direction perpendicular to the horizontal plane, such as Figure 4 The peeling test was performed. The experimental results are shown in Table 3.
[0070] Table 3 Battery cell peel strength test data statistics
[0071] Insulation glue name The peel strength of the first group / N The peel strength of the second group / N First insulation glue 58.37 57.92 Second insulation glue 60.66 60.32 Third insulation glue 55.06 43.89 Fourth insulation glue 57.32 56.32 Fifth insulation glue 58.57 57.73 Sixth insulation glue 45.37 46.78 Seventh insulation glue 48.55 47.31 Eighth insulation glue 38.29 37.78 Ninth insulation glue 34.52 33.45
[0072] The experimental results are shown in Table 3. The peeling strength of the battery cell prepared with the insulating glue in the embodiment of the present application is significantly higher than that of the battery cell prepared with the insulating glue in the comparative example. The peeling strength of the battery cell prepared with the insulating glue in the embodiment of the present application can even reach 60N, that is, the insulating glue in the embodiment of the present application has excellent adhesion to the battery.
[0073] Figure 5 This is a schematic diagram of the peel strength test results of the first insulating glue prepared in Example 1. Figure 6 Schematic diagram of the peel strength test results of the sixth insulating glue prepared in comparative example 1. Figure 5 and Figure 6 As shown, during the peeling process of the battery sheet prepared with the first insulating glue, part of the battery is peeled off together with the glue; while during the peeling process of the sixth insulating glue, the glue film is separated from the glue. That is, the insulating glue in the embodiment of the present application has a better bonding force with the battery. Therefore, the insulating glue provided by the present application can solve the problem of low bonding force between the insulating glue and the battery.
[0074] The present application provides an insulating glue, a preparation method thereof and a photovoltaic module. The insulating glue includes polyurethane acrylate, isobornyl acrylate, a modified monomer, an initiator, a defoamer, a leveling agent and a transparent inorganic material. The transparent inorganic material is fumed silica, the modified monomer includes tetrahydrofuran acrylate and polyethylene glycol monomethacrylate phosphate, the initiator includes 2,4,6-trimethylbenzoyl diphenyl phosphine oxide, the defoamer includes fatty acid esters, the leveling agent includes isophorone, and the insulating glue also includes a silane coupling agent. A leveling agent is added to the glue to improve the fluidity and leveling of the glue, so that the glue can be combined with the uneven surface when printed on the back of the battery (before curing); a low Tg functional resin is added to the glue, so that the cured glue becomes soft and slightly dissolved after high-temperature curing, and further fills and combines with the battery surface, thereby increasing the bonding strength between the glue and the battery and solving the problem of low bonding strength between the insulating glue and the battery.
[0075] The present application also provides a preparation method of the above-mentioned insulating glue and a photovoltaic module, wherein the photovoltaic module is a BC module, and the above-mentioned insulating glue is applied. The photovoltaic BC module is a type of solar photovoltaic panel, and its positive and negative fine grids are alternately distributed on both sides of the main grid, and the distance between adjacent positive and negative electrodes is close. The above-mentioned insulating glue is applied between the positive and negative electrodes of the back contact battery to ensure insulation between the positive and negative electrodes, and effectively prevent the welding strip from contacting the opposite fine grid to form a short circuit during welding. The printing glue screen of the present application is as follows Figure 7 As shown, the solid line frame part is the printing screen, the horizontal solid line and the horizontal dotted line are both fine grid lines, and the dotted line frame is the pad.
[0076] Similar parts between the embodiments provided in this application can be referenced to each other. The specific implementation methods provided above are only a few examples under the general concept of this application and do not constitute a limitation on the protection scope of this application. For those skilled in the art, any other implementation methods expanded based on the scheme of this application without creative work belong to the protection scope of this application.
Claims
1. An insulating glue, characterized in that: The insulating glue comprises polyurethane acrylate, isobornyl acrylate, modified monomer, initiator, defoamer, leveling agent and transparent inorganic material. The mass fraction of polyurethane acrylate in the insulating glue is 55-67%, the mass fraction of isobornyl acrylate is 1-10%, the mass fraction of modified monomer is 10-20%, the mass fraction of initiator is 1-4%, the mass fraction of defoamer is 0.1-0.3%, the mass fraction of leveling agent is 1-3%, and the mass fraction of transparent inorganic material is 3-6%.
2. The insulating glue according to claim 1, characterized in that: The transparent inorganic material is fumed silica.
3. The insulating glue according to claim 2, characterized in that: The insulating glue also includes a silane coupling agent, and the mass fraction of the silane coupling agent in the insulating glue is 0.5-2%.
4. The insulating glue according to claim 1, characterized in that: The modified monomers include tetrahydrofuran acrylate and polyethylene glycol monomethacrylate phosphate. In the insulating glue, the mass fraction of tetrahydrofuran acrylate is 5-10%, and the mass fraction of polyethylene glycol monomethacrylate phosphate is 5-10%.
5. The insulating glue according to claim 1, characterized in that: The initiator includes 2,4,6-trimethylbenzoyldiphenylphosphine oxide.
6. The insulating glue according to claim 1, characterized in that: The defoaming agent includes fatty acid ester, and the leveling agent includes isophorone.
7. A method for preparing insulating glue, characterized in that: The preparation of the insulating glue according to any one of claims 1 to 6 specifically comprises: Polyurethane acrylate, isobornyl acrylate, modified monomer, defoamer, leveling agent, transparent inorganic material and other additives are uniformly mixed according to proportion, heated and stirred to obtain a slurry to be initiated; The initiator is added dropwise to the slurry to be initiated, and the insulating glue is obtained after stirring.
8. The method according to claim 7, characterized in that The method specifically comprises: After uniformly mixing polyurethane acrylate, tetrahydrofuran acrylate, polyethylene glycol monomethacrylate phosphate, isobornyl acrylate, fatty acid ester, isophorone and other additives in a four-necked flask according to a certain proportion, heating to 60-90° C. in an oil bath, stirring for 2-3 hours, slowly dropping a prepolymer of fumed silica and a silane coupling agent to obtain a slurry to be initiated; After the slurry to be initiated is stirred for 1 to 2 hours, 2,4,6-trimethylbenzoyldiphenylphosphine oxide is added dropwise to the slurry to be initiated, and stirred for 1 to 2 hours to obtain the insulating glue.
9. The method according to claim 8, characterized in that The method is operated in the dark, and the speed of adding 2,4,6-trimethylbenzoyldiphenylphosphine oxide is 2s / drop.
10. A photovoltaic module, characterized in that: The photovoltaic module is a BC module, and the photovoltaic module comprises the insulating glue according to any one of claims 1 to 6.